2017
DOI: 10.3390/v9080221
|View full text |Cite
|
Sign up to set email alerts
|

Changing Stem Cell Dynamics during Papillomavirus Infection: Potential Roles for Cellular Plasticity in the Viral Lifecycle and Disease

Abstract: Stem cells and cellular plasticity are likely important components of tissue response to infection. There is emerging evidence that stem cells harbor receptors for common pathogen motifs and that they are receptive to local inflammatory signals in ways suggesting that they are critical responders that determine the balance between health and disease. In the field of papillomaviruses stem cells have been speculated to play roles during the viral life cycle, particularly during maintenance, and virus-promoted ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 68 publications
0
10
0
1
Order By: Relevance
“…Recent studies also support a potential role for stem cells in viral persistence and oncogenesis [ 10 ]. Infection of a stem cell is much more likely to give rise to long-term infection than that of a transit amplifying cell [ 11 ].…”
Section: Natural History Of Hpv Infectionmentioning
confidence: 99%
“…Recent studies also support a potential role for stem cells in viral persistence and oncogenesis [ 10 ]. Infection of a stem cell is much more likely to give rise to long-term infection than that of a transit amplifying cell [ 11 ].…”
Section: Natural History Of Hpv Infectionmentioning
confidence: 99%
“…Notably, we identified the reservoir of HPV in non-neoplastic epithelial cells within the crypts of colonic normal mucosa adjacent to the neoplastic mucosa and we demonstrated that these cells were stem-cells, which are known to be susceptible to transformation by HPV 16 (39, 40). It can be argued that following inflammatory response to a number of stimuli (also including dysbiosis) (41), non-cancer stem cells may be activated into cancer stem cells, sustaining a feed-forward circuit of self-renewal, proliferation, differentiation and neoplastic transformation in a condition of immune evasion, as previously demonstrated (40, 4244). Due to the pluripotency of stem-cells, a squamous cell carcinoma may arise also in colorectal mucosa in the absence of any metaplastic changes, as in our case.…”
Section: Discussionmentioning
confidence: 79%
“…Hence, hepatitis B virus (HBV) harms liver progenitor cells and elicits hepatocellular carcinoma (HCC) [ 9 , 10 ]. HPV disturbs progenitor cells in the epidermal tissues and causes squamous cell carcinoma in the cervix and penis [ 11 ]. Epstein–Barr virus (EBV) disrupts progenitor cells in the head and neck and causes nasopharyngeal carcinoma (NPC) [ 12 ].…”
Section: Virally Induced Malignanciesmentioning
confidence: 99%
“…Hence, when HPV infects a progeny differentiated cervical cell, the affected cell dies and disappears along with the viruses (similar to HAV). However, when HPV infects a progenitor cervical cell with stem-like properties, the infection may perpetuate and malignancy eventuate (similar to HBV) [ 11 ].…”
Section: Hpv and Cervical Cancermentioning
confidence: 99%